Enhancing DNA metabarcoding performance and applicability with bait capture enrichment and DNA from conservative ethanol. (18th September 2019) - Gauthier, Mailys; Konecny‐Dupré, Lara; Nguyen, Agnès; Elbrecht, Vasco; Datry, Thibault; Douady, Christophe; Lefébure, Tristan
Abstract: Metabarcoding is often presented as an alternative identification tool to compensate for coarse taxonomic resolution and misidentification encountered with traditional morphological approaches. However, metabarcoding comes with two major impediments which slow down its adoption. First, the picking and destruction of organisms for DNA extraction are time and cost consuming and do not allow organism conservation for further evaluations. Second, current metabarcoding protocols include a PCR enrichment step which induces errors in the estimation of species diversity and relative biomasses. In this study, we first evaluated the capacity of capture enrichment to replace PCR enrichment using controlled freshwater macrozoobenthos mock communities. Then, we tested if DNA extracted from the fixative ethanol (etDNA) of the same mock communities can be used as an alternative to DNA extracted from pools of whole organisms (bulk DNA). We show that capture enrichment provides more reliable and accurate representation of species occurrences and relative biomasses in comparison with PCR enrichment for bulk DNA. While etDNA does not permit to estimate relative biomasses, etDNA and bulk DNA provide equivalent species detection rates. Thanks to its robustness to mismatches, capture enrichment is already an efficient alternative to PCR enrichment for metabarcoding and, if coupled to etDNA, is a time‐saver option in studies where presence information only is sufficient.